201 Japanese verbs : - Lange, Roland A. (Barron’s Educational Series, 1971)
This book consists of the following such as explanation of Japanese pronunciation and romanization, speech levels in Japanese, inflection and derivation of Japanese verbs, sample conjugation of class I, II verb, and fully described in all inflections, moods, aspects and formality levels.